Evaluation of the impact of the COVID-19 pandemic on health service utilization in China: A study using auto-regressive integrated moving average model - Xu, Rixiang; Wu, Lang; Liu, Yulian; Ye, Yaping; Mu, Tingyu; Xu, Caiming; Yuan, Huiling (Frontiers in Public Health, 2023)
Background: The outbreak of COVID-19 in early 2020 presented a major challenge to the healthcare system in China. This study aimed to quantitatively evaluate the impact of COVID-19 on health services utilization in China in 2020. Methods: Health service-related data for this study were extracted from the China Health Statistical Yearbook. The Auto-Regressive Integrated Moving Average model (ARIMA) was used to forecast the data for the year 2020 based on trends observed between 2010 and 2019. The differences between the actual 2020 values reported in the statistical yearbook and the forecast values from the ARIMA model were used to assess the impact of COVID-19 on health services utilization. Results: In 2020, the number of admissions and outpatient visits in China declined by 17.74% and 14.37%, respectively, compared to the ARIMA model's forecast values. Notably, public hospitals experienced the largest decrease in outpatient visits and admissions, of 18.55% and 19.64%, respectively. Among all departments, the paediatrics department had the greatest decrease in outpatient visits (35.15%). Regarding geographical distribution, Beijing and Heilongjiang were the regions most affected by the decline in outpatient visits (29.96%) and admissions (43.20%) respectively. Conclusion: The study’s findings suggest that during the first year of the COVID-19 pandemic, one in seven outpatient services and one in six admissions were affected in China. Therefore, there is an urgent need to establish a green channel for seeking medical treatment without spatial and institutional barriers during epidemic prevention and control periods.